In vivo assessment of tumour angiogenesis in colorectal cancer: the role of confocal laser endomicroscopy. (2nd February 2016) - De Palma, G. D.; Maione, F.; Esposito, D.; Luglio, G.; Giglio, M. C.; Siciliano, S.; Gennarelli, N.; Cassese, G.; Campione, S.; D'Armiento, F. P.; Bucci, L.
Abstract: Aim: Tumour neoangiogenesis is a key factor in tumour progression and metastatic spread and the possibility to assess tumour angiogenesis might provide prognostic information. The aim of this study was to establish the role of probe‐based confocal laser endomicroscopy (p‐CLE) in the identification of vascular architecture and specific morphological patterns in normal colorectal mucosa and malignant lesions during routine endoscopy. Method: Fourteen consecutive patients with colorectal cancer were included. The following features were identified and then compared between normal and neoplastic mucosa on p‐CLE images: vessel shape (straight vs irregular) vessel diameter the 'branching patterns' vessel permeability (fluorescein leakage) and blood flow (normal vs defective flux). Immunohistochemistry was used to confirm the presence and to study the morphology of vascular structures (CD‐34 staining) and 'neo‐vessels' (WT‐1 staining) on tumour and normal mucosal sections. Results: Tumour vessels appeared as irregular, ectatic and with a highly variable calibre and branching patterns on p‐CLE images. The mean diameter of tumour vessels was significantly larger than those in normal mucosa (weighted mean difference 3.38, 95% CI 2.65–4.11, P = 0.01). Similarly, 'vessel branching' (OR 2.74, 95% CI 1.23–6.14, P = 0.01), fluorescent dye 'extravasation' (OR 3.46, 95% CI 1.39–8.57, P = 0.01) were significantly more frequent in colorectal cancer than in normal colorectal mucosa. Immunohistochemistry corroborated the p‐CLE findings, showing higher vascularity in tumour sections due to neoformed vessels, presenting irregular patterns. Conclusion: Probe‐based confocal laser endomicroscopy provides a noninvasive characterization of the microvascular architecture of colonic mucosa. Different morphological patterns have been described, discriminating normal and malignant microvascular networks in colorectal mucosa.